Legal Responsibility in Environmental Law - Niculescu Iuliana (Journal of Danubian Studies and Research, 2018)
The paper aims to make an endeavor in the field of environmental law. It is recognized that the most important role in the field of environmental protection and nature conservation is played by the preventive means of civil or administrative nature, while the criminal law means have a subsidiary role, which is why we have analyzed the civil, contraventional and criminal liability.